Pandoravirus Celtis Illustrates the Microevolution Processes at Work in the Giant Pandoraviridae Genomes - Legendre, Matthieu; Alempic, Jean-Marie; Philippe, Nadège; Lartigue, Audrey; Jeudy, Sandra; Poirot, Olivier; Ta, Ngan Thi; Nin, Sébastien; Couté, Yohann; Abergel, Chantal; Claverie, Jean-Michel (Frontiers in Microbiology, 2019)
With genomes of up to 2.7 Mb propagated in µm-long oblong particles and initially predicted to encode more than 2000 proteins, members of the Pandoraviridae family display the most extreme features of the known viral world. The mere existence of such giant viruses raises fundamental questions about their origin and the processes governing their evolution. A previous analysis of six newly available isolates, independently confirmed by a study including 3 others, established that the Pandoraviridae pan-genome is open, meaning that each new strain exhibits protein-coding genes not previously identified in other family members. With an average increment of about 60 proteins, the gene repertoire shows no sign of reaching a limit and remains largely coding for proteins without recognizable homologs in other viruses or cells (ORFans). To explain these results, we proposed that most new protein-coding genes were created de novo, from pre-existing non-coding regions of the G+C rich pandoravirus genomes. The comparison of the gene content of a new isolate, pandoravirus celtis, closely related (96 % identical genome) to the previously described p. quercus is now used to test this hypothesis by studying genomic changes in a microevolution range. Our results confirm that the differences between these two similar gene contents mostly consist of protein-coding genes without known homologs (ORFans), with statistical signatures close to that of intergenic regions. These newborn proteins are under slight negative selection, perhaps to maintain stable folds and prevent protein aggregation pending the eventual emergence of fitness-increasing functions. Our study also unraveled several insertion events mediated by a transposase of the hAT family, 3 copies of which are found in p. celtis and are presumably active. Members of the Pandoraviridae are presently the first viruses known to encode this type of transposase.